2020
DOI: 10.11648/j.ijafrm.20200502.11
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Finance Biases in Investment Decision Making

Abstract: Traditional finance suggests that investments made by rational behaviors investors examine risk and return before decision making to gain maximum profit later behavioral finance challenge traditional finance and introduce psychological factors affect decision making. The aim of this research paper is to explore how behavioral biases affect investment decision making under uncertainty. Dependent variable investment decision making is a composite activity, it never be made in a vacuity by depending on personal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 2 publications
2
35
0
3
Order By: Relevance
“…Investors tend to and need to focus on factors that help them to make rational decisions, which maximize their return at lower risk and cost without involving emotional feelings in financial decision making (Brabazon, 2001;Shah, et al, 2018). A recent study by Atif Sattar, Toseef and Fahad Sattar, (2020) suggested that behavioral biases have a significant effect on investment decisions and it is therefore noteworthy to explore these dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Investors tend to and need to focus on factors that help them to make rational decisions, which maximize their return at lower risk and cost without involving emotional feelings in financial decision making (Brabazon, 2001;Shah, et al, 2018). A recent study by Atif Sattar, Toseef and Fahad Sattar, (2020) suggested that behavioral biases have a significant effect on investment decisions and it is therefore noteworthy to explore these dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Loomes and Sugden (1982) came up with the first definition of regret aversion and explained that it motivates individuals to prevent future regret. According to Sattar et al (2020), regret aversion means that the investor never wants to regret inefficient investment decisions. Chen et al (2018) investigated that during decision making, the human response often encounters regret aversion preferences and decision makers feel regret if they make the wrong decision.…”
Section: Theoretical Background Prospect Theorymentioning
confidence: 99%
“…There are several fallacies that act as barriers in one's ability to engage in logical and mature decision making. Sattar, Toseef and Sattar (2020) [18] conducted a quantitative study to test the role of heuristics (representativeness, anchoring, overconfidence etc. ), personality characteristics (extraversion, agreeableness, neuroticism etc), prospect theory components (framing, regret aversion, self-control etc.)…”
Section: Section II Literature Reviewmentioning
confidence: 99%
“…The results from the analysis showed that investor sentiment is an important concept studied in both traditional and behavioural finance theories. Sattar, Toseef and Sattar (2020) [18] studied the role of several behavioural biases in the investment decisions made in the market. They used regression analysis to investigate the impact of heuristic, prospects and personality characteristics on the investor's behaviour.…”
Section: Section II Literature Reviewmentioning
confidence: 99%